Drawing to improve metacomprehension accuracy. (February 2022) - Thiede, Keith W.; Wright, Katherine L.; Hagenah, Sara; Wenner, Julianne; Abbott, Jadelyn; Arechiga, Angela
Abstract: We examined the effect of drawing sketches on metacomprehension accuracy of science texts for 5th grade (ages 10–11) students (Study 1: N = 60, Study 2: N = 62). Students either received instruction on drawing organizational sketches, which focused on capturing the relationships described in texts, or representational sketches, which focused on capturing details described in texts. They then read and drew sketches for texts, predicted their performance, and completed tests. They completed this procedure for five texts. Metacomprehension accuracy was greater for students instructed to draw organizational sketches than for students instructed to draw representational sketches or those in a control group who did not draw (Study 2). Performance on comprehension tests was also greater for students instructed to draw organizational sketches than for students in other groups. The superior metacomprehension accuracy was explained in terms of the cue-utilization framework of metacognitive monitoring (Koriat, 1997). Highlights: Generating organizational drawings improved metacomprehension accuracy. Generating organizational drawings improved reading comprehension. Drawing relations metrics were related to performance on comprehension tests. Drawing relations metrics were related to metacomprehension judgments. Cue utilization can help explain differences in metacomprehension accuracy.